Respuestas

  • Usuario de Brainly
2013-11-07T22:31:09+01:00
Solución:
1) (2x - 3)^3 = (2x)^3 - 3(2x)^2(3) + 3(2x)(3)^2 - (3)^3
..................= 8x^3 - 36x^2 + 54x - 27 000>RESPUESTA.

2) (x + 2)^3 =  (x)^3 + 3(x)^2(2) + 3(x)(2)^2 + (2)^3
.................=   x^3  + 6x^2 + 12x + 8====>RESPUESTA.

3) (3x - 2)^3 = (3x)^3 - 3(3x)^2(2) + 3(3x)(2)^2 - (2)^3
..................= 27x^3 - 54x^2 + 36x - 8 =====>RESPUESTA.

4) (2x + 5)^3 = (2x)^3 + 3(2x)^2(5) + 3(2x)(5)^2 + (5)^3
...................= 8x^3 + 60x + 150x + 125 ====>RESPUESTA

Espero haberte ayudado. Suerte.